FETAL ABNORMALITIES IN SWINE: A STUDY UNDER FIELD AND ORGANIZED FARM CONDITIONS - KUMARESAN, A (The Indian Journal of Animal Reproduction, 2023)
Fetal abnormalities in pigs cause heavy loss to the farmer as it reduces the return from sale of piglets, reduction in availability of replacement stocks and the associated loss in the lifetime production and reproduction of sows. This article deals with different fetal abnormalities encountered over a period in pigs reared under field as well as organized farm conditions. The fetal abnormalities in pigs encountered in the present study were anophthalmos, ascites, anasarca, atresia ani, mummification, maceration, syndactyly like condition, splay leg, hemorrhagic fetus, leg malformations etc. The etiology and management options are also discussed.